Exploring parental involvement in early childhood education in Sub-Saharan Africa: A systematic review - Winifrida Kambona (Social Sciences and Humanities Open)
Early Childhood Education (ECE) has gained a global momentum, with increasing recognition of its importance for children’s academic success in schools. Parents play a significant role in supporting children’s acquisition of ECE as they are the first teachers. Despite parents’ significant contributions to their children’s learning and development, systematic review studies on parental engagement in ECE and the barriers they face in Sub-Saharan African countries remain scarce. This study explores the strategies employed by parents to engage in their children’s ECE and the challenges they face in Sub-Saharan Africa. A systematic review was conducted based on the PRISMA model. Two electronic databases were used to search for the articles involved in the review process, including Dimensions and Scopus. Out of the 1,040 articles initially identified, only 13 met the established inclusion criteria. A thematic synthesis method was used to analyse the data from the reviewed articles, whereby major themes were developed based on the research questions and data generated. The findings indicate that parents utilized varied ways in participating in their children’s education including engaging in children’s academic activities, provision of school needs and attending school meetings. Nonetheless, a number of barriers were revealed to encounter parents such as low levels of education, low socio-economic status, and cultural constraint. The study concludes that parental involvement in children’s ECE is essential for children’s overall development and school readiness. It was recommended to the policy makers that supportive policy guidelines should be developed to help parents in engagement in their children’s ECE. Parents should be educated on the importance of involvement in children’s early learning experiences. Moreover, the governments in Sub-Saharan Africa should provide support to children from poor families.